Marcas & Signos : a recepção dos sinais não convencionais pelo Brasil. - Azevedo Filho, Valberto Alves de. (2016)
The present paper intends to inquire the national policy behind trademarks on the ground of nonconventional symbols, from trademark history to a comparative analysis between Brazil¿s law system and the United States of America¿s, along side the international treatises which Brazil is bound by, such as the Paris Convention and TRIPS. Throughout this comparison, the work will show how Brazilian law system disrespects its own Constitution, and goes the other way from the international regulation of trademarks when restricts its protections only to symbols that are visual perceived, letting behind other kinds of symbols which accomplish the same goals. As a result, the paper proposes changes in Brazilian law to protect these nonconventional symbols (as to say, nonvisual symbols) in order to reach an harmony with the international law, no matter how these symbols can be perceived. By protecting such nonconventional symbols, fair trade will be assured and more consumers will be included in the market, as they have the right to be informed about the different products and services offered to them.